Facile synthesis of CdZnS QDs: Effects of different capping agents on the photoluminescence properties. (July 2018) - Masab, Muhammad; Muhammad, Haji; Shah, Faheem; Yasir, Muhammad; Hanif, Muddasir
Abstract: The luminescent semiconductor QDs are important materials because of applications in lasers, sensors, light-emitting diodes, biomedical labeling, biomedical imaging and solar cells. We have systematically studied the influence of five different capping agents on the structural and optical characteristics of CdZnS quantum dots (QDs) synthesized by the simplest aqueous method. The modified QDs were characterized by the UV–visible spectroscopy, X-ray diffraction, steady-state photoluminescence (PL), time-resolved PL, and transmission electron microscopy. We found that band-gap and PL characteristics of CdZnS QDs can be varied by using different capping agents. The CdZnS QDs capped with ethylene diamine (EDA) and mercaptoacetic acid (MAA) showed high PL intensities when compared to other capping agents. The UV–Vis absorption spectra were used to calculate the optical band-gaps: 2.63 eV (MAA), 2.56 eV (MPA), 2.42 eV (CA), 2.64 eV (Glucose) and 2.62 eV (EDA) of five different QDs: The time-resolved PL spectroscopy indicated slowest bi-exponential fluorescence decay rate for the MAA-capped CdZnS (CdZnS-MAA) QDs.